Pengembangan Alat Evaluasi HOTS Berbasis BOT Telegram pada Materi Larutan Penyangga - Asriana, Asriana; Auliah, Army; Hardin, Hardin (Universitas Negeri Gorontalo, 2023)
The purpose of this study was to develop a HOTS evaluation tool for quality BOT telegram-based buffer solution material to be used in learning evaluation activities. This evaluation tool was developed using the Borg & Gall model. This research took place in the even semester of the 2021-2022 academic year at SMAN 7 Soppeng. The subjects in this study were 31 students of class XI MIPA 1 SMAN 7 Soppeng. The research instruments used were expert validation sheets, student response questionnaires and learning outcomes tests. Based on the validation results from material experts and media experts, it shows that the evaluation tool developed is very valid with a percentage of validity, namely 86% in terms of material and 86.88% in terms of media. Then based on the results of the analysis in terms of practicality, it shows that the HOTS evaluation tool developed is practical with a practicality percentage of 73.5%. Thus, the HOTS evaluation tool developed is said to be qualified based on quality criteria which include valid and practical. So, the BOT telegram-based HOTS evaluation tool is feasible to use as a learning evaluation tool on buffer solution material.